Factors Associated with Nasal Mucociliary Clearance Time in Elderly Nursing Home Residents - Baros, Wan Andre Nugraha Baros; Munir, Delfitri; Zahara, Devira; Nursiah, Siti; Farhat, Farhat; Ashar, Taufik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The mucociliary transport system is an essential defense mechanism of the nasal cavity that helps remove pathogens, allergens, and particles. Impairment of this system may prolong mucociliary clearance time (MCT) and increase susceptibility to infection. Aging and systemic conditions may influence mucociliary function. This study aimed to evaluate the association between age, gender, diabetes mellitus, hypertension, and smoking history with nasal mucociliary clearance time in elderly individuals. An analytical cross-sectional study was conducted in a nursing home in Medan over three months. A total of 40 elderly participants were included. Nasal mucociliary clearance time was measured using the saccharin test. Data were analyzed using the Chi-square test. The mean mucociliary clearance time was 16.45 minutes. A significant association was found between age and MCT, as well as between gender and MCT, with males showing better clearance time than females. No significant associations were observed between MCT and diabetes mellitus, hypertension, or smoking history. Age and gender are significantly associated with nasal mucociliary clearance time in the elderly, while diabetes mellitus, hypertension, and smoking history are not. These findings suggest that physiological aging and gender-related differences may influence nasal defense mechanisms, highlighting the importance of considering these factors in respiratory health assessment in the elderly.